(untitled) (The Shivapuri Journal, 2024)
The essay delves into Nepal’s substantial involvement in UN peacekeeping, particularly examining the Nepali Army’s role in Operation Lifeline within the UN Mission in South Sudan (UNMISS). It traces the historical origins of Operation Lifeline Sudan (OLS) and its transformation into Operation Lifeline (OLL) within UNMISS, emphasizing Nepal’s enduring commitment to global peace. The narrative focuses on OLL-54, where the Nepali High Readiness Company (NEPHRC) played a crucial role, exceeding agreed-upon limits to ensure the safe passage of the barge in a complex security situation. The essay underscores the operational credibility and professionalism of the Nepali contingents especially NEPHRC, suggesting it as a case for Nepal’s unique contribution to future UN peacekeeping efforts. It advocates for the systematic documentation of such experiences, envisioning the development of a unique Nepali peacekeeping model for the world. In conclusion, the essay asserts that Nepal has an opportunity to showcase its commitment and achievements in international peacekeeping, reinforcing its position as a significant contributor to the evolving landscape of UN peace missions. Nepali Army’s (NA) six decades in United Nations (UN) peacekeeping is a reflection of Nepal’s enduring commitment to global peace and security. This is not merely a legacy or an aggregate of numbers of participation, achievements, and sacrifices. NA today carries a huge baggage of experience and knowledgebase derived from different peacekeeping environments of conflict zones across the world from as many as 44 traditional and multi-dimensional UN peacekeeping missions. Quite significantly, NA can offer the UN a Nepali peacekeeping model based on lessons acquired through involvement and practice. From each mission and (the number of) contingents in those missions, NA has gathered tremendous lessons and learning (experience) from individuals - leaders and men alike and participating units. Yet very few attempts were made to collect those experiences and bring about inferences for its future application. The author believes that Nepal can contribute to the world with a unique outlook for future UN peacekeeping, which is always evolving. This paper, however, only attempts to discuss Operation Lifeline (OLL) of the United Nations Mission in South Sudan (UNMISS) in particular to derive lessons relevant for Nepal/NA to consider for the future.